2023
DOI: 10.1002/adfm.202313755
|View full text |Cite
|
Sign up to set email alerts
|

A Bioactive Photosensitizer for Hypoxia‐Tolerant Molecular Targeting‐Photo‐Immunotherapy of Malignant Tumor

Lianfeng Fan,
Chuanjiang Jian,
Ling Li
et al.

Abstract: Photosensitizers (PSs) with effective reactive oxygen species generation ability against hypoxia are of great potential for clinical treatment of malignant tumors. However, complex tumor microenvironment, such as antioxidative responses and immunosuppression, would ineluctably limit the efficiency of photodynamic therapy (PDT). Herein, a molecular‐targeting photosensitizer QTANHOH is rationally designed for histone deacetylases (HDACs‐targeting photo‐immunotherapy application. The PS QTANHOH displays excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…20 Our study demonstrated that it is feasible to combine photosensitizers with targeted bioactive pharmacophores to design bioactive photosensitizers that simultaneously exert photodynamic and chemotherapy effects. Based on the above discussion, as well as our previous work on quinoxalinone skeleton based photosensitizers that usually show good light harvesting and photosensitization efficiencies, 20,42,43 herein, we further propose a design strategy for DNA targeted bioactive photosensitizers, aiming at chemophotodynamic synergistic therapy via single-molecule integration of DNA-targeting chemotherapy drugs and photosensitizers. The main design concept involves (1) the incorporation of chlormethine as a DNA alkylating chemotherapeutic moiety to effectively target DNA and damage DNA through a cross-linking reaction; (2) the integration of dimethylamino into the molecule to further enhance the interaction between the photosensitizer and DNA (please see the binding free energy results in Table S1) and improve hydrophily (please see the oil−water partition coefficients (log P) in Table S1); (3) the introduction of the anthraquinone group with good redox properties, serving as electron acceptor to promote the electron transfer, 44,45 thereby facilitating the efficient production of type-I ROS (Figure 1A and B).…”
mentioning
confidence: 97%
“…20 Our study demonstrated that it is feasible to combine photosensitizers with targeted bioactive pharmacophores to design bioactive photosensitizers that simultaneously exert photodynamic and chemotherapy effects. Based on the above discussion, as well as our previous work on quinoxalinone skeleton based photosensitizers that usually show good light harvesting and photosensitization efficiencies, 20,42,43 herein, we further propose a design strategy for DNA targeted bioactive photosensitizers, aiming at chemophotodynamic synergistic therapy via single-molecule integration of DNA-targeting chemotherapy drugs and photosensitizers. The main design concept involves (1) the incorporation of chlormethine as a DNA alkylating chemotherapeutic moiety to effectively target DNA and damage DNA through a cross-linking reaction; (2) the integration of dimethylamino into the molecule to further enhance the interaction between the photosensitizer and DNA (please see the binding free energy results in Table S1) and improve hydrophily (please see the oil−water partition coefficients (log P) in Table S1); (3) the introduction of the anthraquinone group with good redox properties, serving as electron acceptor to promote the electron transfer, 44,45 thereby facilitating the efficient production of type-I ROS (Figure 1A and B).…”
mentioning
confidence: 97%